1984
DOI: 10.1080/03036758.1984.10421738
|View full text |Cite
|
Sign up to set email alerts
|

The density of indigenous invertebrates on three islands in Breaksea Sound, Fiordland, in relation to the distribution of introduced mammals

Abstract: The density of indigenous invertebrates was sampled on three islands in Fiordland which have similar soils, vegetation and climate, and presumably also originally had similar invertebrate faunas. Resolution Island (20,860 ha) now supports stoats and deer, and Breaksea Island (150 ha) has Norway rats; Gilbert Island No.6 (20 ha) is still completely free of mammals. Compared with Gilbert No.6, the densities of 13 groups of invertebrates were lower on Breaksea, and the densities of 2 groups were lower on Resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Its freedom from rats is considered to account for the high diversity and abundance of invertebrates recorded there, particularly the larger ground-dwelling species (Barratt et al, 1986). Similar results were also recorded on the small (20 ha) Gilbert No.6 Island in Breaksea Sound 40 km to the south, which remains free of all introduced mammals (Bremner et al, 1984). It is also important to note that modification of Secretary 1.…”
Section: Discussionsupporting
confidence: 68%
“…Its freedom from rats is considered to account for the high diversity and abundance of invertebrates recorded there, particularly the larger ground-dwelling species (Barratt et al, 1986). Similar results were also recorded on the small (20 ha) Gilbert No.6 Island in Breaksea Sound 40 km to the south, which remains free of all introduced mammals (Bremner et al, 1984). It is also important to note that modification of Secretary 1.…”
Section: Discussionsupporting
confidence: 68%
“…When the density of invertebrates was estimated on this, and a nearby smaller island (Gilbert Island No. 6,20 ha) which was free of all introduced mammals, it was found that all taxonomic groups, except small weevils, had declined (Bremner et al 1984). The authors' survey of indigenous invertebrates, which were heat-extracted from litter, moss and rotten wood, showed that for every 100 invertebrates caught on Breaksea Island, 173 were found on Gilbert No.…”
Section: A Comparative Island Study In Breaksea Sound Fiordlandmentioning
confidence: 94%
“…6, but only fragments on Breaksea, suggesting that this species was recently present there but could no longer be found alive. Bremner et al (1984) concluded that 'predation by Norway rats is having a devastating effect on the population density of many invertebrate groups on Breaksea Island' and that the most vulnerable are large beetles, weta, harvestmen and 'some unexpectedly small species'.…”
Section: A Comparative Island Study In Breaksea Sound Fiordlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitaker 1973Towns and Daugherty 1994;Cree et al 1995), large invertebrates (e.g. Ramsey 1978;Bremner et al 1984), and mammals (e.g. Burbidge and Manly 2002) as a result of predation by rats.…”
Section: Introductionmentioning
confidence: 99%